Exercise partly reverses the effect of maternal separation on hippocampal proteins in 6‐hydroxydopamine‐lesioned rat brain. Issue 1 (10th July 2012) - Dimatelis, J. J.; Hendricks, S.; Hsieh, J.; Vlok, N. M.; Bugarith, K.; Daniels, W. M. U.; Russell, V. A.
Abstract : Animals subjected to maternal separation stress during the early stages of development display behavioural, endocrine and growth factor abnormalities that mirror the clinical findings in anxiety/depression. In addition, maternal separation has been shown to exacerbate the behavioural deficits induced by 6‐hydroxydopamine (6‐OHDA) in a rat model of Parkinson's disease. In contrast, voluntary exercise reduced the detrimental effects of 6‐OHDA in the rat model. The beneficial effects of exercise appeared to be largely due to compensation in the non‐lesioned hemisphere. The aim of the present study was to investigate whether voluntary exercise for 3 weeks could reverse the effects of maternal separation in rats challenged with the neurotoxin 6‐OHDA infused into the medial forebrain bundle after 1 week of exercise, at postnatal day 60. The rats were killed 2 weeks later, at postnatal day 74. Their brains were dissected and the hippocampus rapidly removed for proteomic analysis by isobaric tagging (iTRAQ) and quantification of peptides by matrix‐assisted laser desorption/ionization tandem mass spectrometry (MALDI‐MS/MS). Maternal separation upregulated hippocampal proteins functionally involved in energy metabolism (nucleoside diphosphate kinase B, enolase and triosephosphate isomerase) and synaptic plasticity (α‐synuclein, tenascin‐R, Ba1‐667, brevican and neurocan core protein) in the non‐lesioned hemisphere. Exercise reversed many of these changes by downregulating the levels of hippocampal proteins functionally associated with energy metabolism (nucleoside diphosphate kinase B, enolase and triosephosphate isomerase) and synaptic plasticity (α‐synuclein, tenascin‐R, Ba1‐667, brevican and neurocan core protein) in the non‐lesioned hemisphere of rats subjected to maternal separation. Exercise and maternal separation therefore appeared to have opposing effects on the hippocampus in the non‐lesioned hemisphere of the rat brain. Exercise seemed partly to reverse the effects of maternal separation stress on these proteins in the non‐lesioned hemisphere. The partial reversal of maternal separation‐induced proteins by exercise in the non‐lesioned side sheds some insight into the mechanism by which exercise alters the molecular role players involved in determining the consequences of early life stress.